Irish and British historical electricity prices and implications for the future - Paul Deane; John FitzGerald; Laura Malaguzzi; Aidan Tuohy; Darragh Walsh (The Economic and Social Research Institute (ESRI), 2013)
This paper compares retail and wholesale electricity prices in SEM, the market of the island of Ireland, and BETTA in Great Britain. Wholesale costs are much lower in BETTA. We show that this is mostly because the wholesale price in BETTA is set too low to cover generation costs, although it is compensated by large retail margins. The substantial need for new investment in generation in Great Britain suggests that returns to generators will have to increase. Developing a market mechanism to compensate generators fairly while simultaneously reducing retail revenue will help in achieving this goal.
Keywords: C63; L94; L98; 330; SEM; BETTA; electricity prices; simulation model